Juvenile Granulosa Cell Tumour: Anaplastic Variant with Omental Deposits - Rao, Anuradha C.K. (J Clin Diagn Res, 2016)
Juvenile Granulosa Cell Tumour (JGCT) of ovary represents a small fraction of all primary ovarian malignancies. It is a subtype of granulosa cell tumour that is almost always found during the first three decades of life. Histologically, it differs from the typical adult type of granulosa cell tumour. It accounts for 5-15% of all granulosa cell tumours, majority being unilateral. Herein, we describe an unusual histopathological variant of JGCT with numerous large cystic spaces, anaplasia and focal syncytiotrophoblast like giant cells.